Ultrasound-mediated degradation of xanthan polymer in aqueous solution: Its scission mechanism and the effect of sodium chloride incorporation / Haziqah Mohd Saleh - Haziqah, Mohd Saleh (2017)
Xanthan gum is a versatile polymer with a wide range of industrial applications. The natural extracellular polymer is synthesized by Xanthomonas sp. from renewable resources. It exhibits superior properties to be used as thickener and stabilizer for emulsions and suspensions. Nonetheless, xanthan gum is practically limited by its own very high molecular weight for specific types of applications such as nano-sized emulsion. Hence, for an even wider range of uses, tailored functionalization through degradation is key to further expand its functionality hence adding more values to the industrial worth polymer. In this study, degradation of xanthan gum in aqueous solution by ultrasonic irradiation was investigated. Ultrasound-mediated process is highly advantageous over other degradation methods such as chemical since it employs acoustic wave to carry out the hydrolysis. Consequently, downstream processing complications in separation and purification steps are drastically minimized. Four sonication parameters were selected to be investigated and optimized in this study viz. sonication intensity, irradiation time, concentration of xanthan gum and molar concentration of NaCl solution. Combined approach of full factorial design and conventional one-factor-at-a-time was applied to obtain the optimum degradation of xanthan polymer. Using degree of degradation (%) as a response, optimum degradation was achieved at sonication power intensity of 11.5 W cm-2, irradiation time 120 min and 0.1 g L-1 xanthan in salt-free solution. Molecular weight reduction of xanthan under sonication was also investigated. The degradation behaviour followed second-order exponential decay function with two different rate constants obtained for different segments of the curve. Molecular weight reduction rate constant of 14.6  10-2 s-1 was determined for the early phase of irradiation, while a slower rate constant of 6.1 x 10-4 s-1 was calculated for a later phase. The limiting molecular weight where fragments no longer undergo scission was also determined from the function. Different limiting molecular weight was observed with respect to sonication conditions where the incorporation of NaCl in xanthan aqueous solution resulted in higher limiting molecular weight. Different scission models were proposed i.e random- and mid-point chain scission models. The ultrasound-mediated degradation of aqueous xanthan polymer agreed with mid-point scission model, and was supported by the molecular weight analysis and thermal decomposition behaviour of sonicated xanthan gum. Side chain of xanthan polymer was proposed to be the primary site of scission action.